‘The Wrestlers’: A Roman mosaic from North Africa - Gordon, Sandra (Buried History: The Journal of the Australian Institute of Archaeology, 2020)
In 2018 the Nicholson Museum, The University of Sydney, acquired a small Roman mosaic known as ‘The Wrestlers’ (NM 2018.135). The mosaic is of North African origin and is almost certainly the product of a local Tunisian workshop during the 3rd century, a period of intense urbanisation and wealthy local patronage in the Roman provinces. The mosaic depicts two athletes in the final stages of a pankratic competition and is framed by a distinctive red and black border, parallels for which are found in mosaics from Gightis near modern Boughrara in southeastern Tunisia. This paper analyses the mosaic within the context of decorative mosaic art and places it chronologically and stylistically within the broader scope of the mosaic industry in Africa Proconsularis.